Analysis of Halfway House Management for Persons with Social Health Problems at the Office of the Social Service of Pasangkayu Regency - Markami, Niswa; Sirajudin, Sirajudin; Rukhayati, Rukhayati (Universitas Muhammadiyah Palu, 2020)
Efforts to deal with people with social welfare problems in Pasangkayu Regency, especially those carried out by Shelter Homes, one of which is managed by the Pasangkayu Regency Social Service, which cares about social welfare issues, includes various activities including guidance for displaced people, victims of acts of violence and trafficking. The halfway house has a vision, mission, programs, management, and facilities and infrastructure that support the guidance carried out by the Halfway House in Pasangkayu Regency. The halfway house under the auspices of the Pasangkayu Regency Social Service has service principles divided into three principles: the basic principles of social workers, the principles of the approach, and the principles of the implementation approach. As a trauma center in Pasangkayu Regency, the halfway house carries out elements of planning, organizing, controlling, and evaluating.